2020
DOI: 10.1108/bij-04-2020-0146
|View full text |Cite
|
Sign up to set email alerts
|

Performance implication of supplier relationship quality: a structural analysis

Abstract: PurposeThis study aims to examine the impact of supplier relationship quality on curtailing opportunism and promoting cooperation between the exchange partners. It also investigates the contingent impact of contract specificity on the relationships and assesses performance implications of relationship quality for both buyer and its major supplier in the exchange.Design/methodology/approachConfirmatory factor analysis and path analysis were performed based on data collected from manufacturers in a survey. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…In reference to H1, it is found that relationship quality has a significant impact on collaboration effects, specifically in the context of the multi-subject collaborative protection of China's ICH. This finding is consistent with studies in other areas, such as education [51], business [52], supply chain collaboration [53], etc. In short, there is a positive connection between the quality of the relationship among participants and the final result.…”
Section: Discussionsupporting
confidence: 92%
“…In reference to H1, it is found that relationship quality has a significant impact on collaboration effects, specifically in the context of the multi-subject collaborative protection of China's ICH. This finding is consistent with studies in other areas, such as education [51], business [52], supply chain collaboration [53], etc. In short, there is a positive connection between the quality of the relationship among participants and the final result.…”
Section: Discussionsupporting
confidence: 92%
“…Building a long-term relationship with both suppliers and customers allows firms to lower transaction costs in terms of searching and contracting costs, while still having reliable transactions (Zhao et al, 2008). External integration would build high quality relationship between the organization and its partners Economic impact of supply chain integration that improve trust and commitment (Yang et al, 2021), reduce potential optimistic behaviors (Yang et al, 2021;Khanuja and Jain, 2020); and improve performance (Kros et al, 2019). Therefore, we develop our hypothesis H3 as follows:…”
Section: Supply Chain Integration and Economic Performancementioning
confidence: 99%
“…Process integration, likely as an internal capability, could be considered a base for the development of external integrative capabilities Huo (2012). High quality relationship with both suppliers and customers could facilitate the integration of process intra-and interorganization (Sundram et al, 2016;Yang et al, 2021). Therefore, external integration would positively mediate the impact of process integration and information integration on economic performance.…”
Section: Supply Chain Integration and Economic Performancementioning
confidence: 99%
“…To reduce uncertainty as in the TCE for online purchases, price and risk reduction become essential to online buyers. Being able to reduce transaction costs and risk will enable businesses to develop relationships with customers and develop longterm relationships, whilst high levels of uncertainty can reduce the chances that a transaction takes place (Tsay et al 2018;Yang et al 2020).…”
Section: Link Between Uncertainty Of Transaction Cost Economics and Price And Risk Reduction In E-business-to-consumer Transactionsmentioning
confidence: 99%
“…Ensuring customer satisfaction and loyalty by developing long-term relationships with them is necessary from an economic (profit) perspective of a business (Yang et al 2020).…”
Section: Uncertaintymentioning
confidence: 99%